Infrasound Array Analysis of Debris Flow Activity and Implication for Early Warning. Issue 2 (14th February 2019) - Marchetti, E.; Walter, F.; Barfucci, G.; Genco, R.; Wenner, M.; Ripepe, M.; McArdell, B.; Price, C.
Abstract : Debris flows constitute a severe natural hazard and studies are performed to investigate triggering mechanisms and to identify and evaluate early warning systems. We present a seismoacoustic analysis of debris flow activity at Illgraben, Switzerland, with infrasound data collected with a small aperture array. Events are recorded as emergent signals of long duration, with seismic and infrasound amplitudes scaling with the flow discharge. The spectral content is stable and peaking at 8 Hz for the seismic and at 5 Hz for the infrasound that suggests two separate processes of elastic energy radiation, most likely bed‐load transport for the seismic and waves at the free surface for the infrasound. Although amplitude and frequency content of the infrasound signal are well within the processing limits, most of the signal is not showing any correlation among the array elements. We suggest that this is a consequence of the contribution of multiple sources of infrasound acting with variable amplitude and phase along the surface of the debris flow. At Illgraben, coherent infrasound is recorded only from fixed sources, corresponding to check dams within the channel. Here infrasound radiation is increased and the dams turn into predominant sources of energy. This allows to unambiguously identify the occurrence of debris flow at Illgraben with the infrasound array, from a remote and safe position and with a timing that is similar to the early warning system based on in‐channel sensors. This clearly shows how infrasound arrays could be used as an efficient early warning systems. Plain Language Summary: Debris flows constitute a severe natural hazard in alpine environments, and studies are currently performed to investigate triggering mechanisms and to identify and evaluate early warning systems. We present a seismoacoustic analysis of debris flow activity at Illgraben, Switzerland, with infrasound data collected for the first time with an array of infrasound sensors deployed outside the channel in a safe position. This seimoacoustic experiment is providing interesting constraints on the mutual radiation of energy in the ground and in the atmosphere by the flow. Moreover, the use of the infrasound antenna allowed for the first time to carefully analyze the mechanism of infrasound radiation that we model as an extended source of energy with variable phase. Moreover, the array is able to detect the debris flow when it crosses dams or topography steps, even if this occurs at large distance (>2 km) and despite not being visible from the recording site. For the specific case of Illgraben, this allows to unambiguously identifying the occurrence of debris flow with a timing that is similar to the early warning system based on in‐channel sensors. This clearly shows how infrasound arrays could be used as new early warning systems for debris flow activity. Key Points: Infrasound array analysis shows that debris flows can be modeled as an extended source of infrasound with variable phase Seismic and infrasound spectra of debris flows at Illgraben are decoupled and suggest two different mechanisms of energy radiation When sharp topography is present, infrasound arrays can be used as an efficient early warning systems for debris flows remotely